Ambient fine particulate matter and ozone pollution in China: synergy in anthropogenic emissions and atmospheric processes. (1st December 2022) - Jiang, Yueqi; Wang, Shuxiao; Xing, Jia; Zhao, Bin; Li, Shengyue; Chang, Xing; Zhang, Shuping; Dong, Zhaoxin
Abstract: Since 2013, China has taken a series of actions to relieve serious PM2.5 pollution. As a result, the annual PM2.5 concentration decreased by more than 50% from 2013 to 2021. However, ozone pollution has become more pronounced, especially in the North China Plain. Here, we review the impacts of anthropogenic emissions, meteorology, and atmospheric processes on ambient PM2.5 loading and components and O3 pollution in China. The reported influence of interannual meteorological changes on PM2.5 and O3 pollution during 2013–2019 ranged from 10%–20% and 20%–40%, respectively. During the same period, the anthropogenic emissions of NO x, SO2, primary PM2.5, NMVOC and NH3 are estimated to decrease by 38%, 51%, 35%, 11% and 17%, respectively. Such emission reduction is the main cause for the decrease in PM2.5 concentration across China. However, the imbalanced reductions in various precursors also result in the variation in nitrate gas-particle partitioning and hence an increase in the nitrate fraction in PM2.5 . The increase of ozone concentration and the enhancement of atmospheric oxidation capacity can also have substantial impact on the secondary components of PM2.5, which partly explained the growth of organic aerosols during haze events and the COVID-19 shutdown period. The uneven reduction in NO x and NMVOC is suggested to be the most important reason for the rapid O3 increase after 2013. In addition, the decrease in PM2.5 may also have affected O3 formation via radiation effects and heterogeneous reactions. Moreover, climate change is expected to influence both anthropogenic emissions and atmospheric processes. However, the extent and pathways of the PM2.5 -O3 interplay and how it will be impacted by the changing emission and atmospheric conditions making the synergetic control of PM2.5 and O3 difficult. Further research on the interaction of PM2.5 and O3 is needed to provide basis for a scientifically-grounded and effective co-control strategy.